Caste-specific RNA editomes in the leaf-cutting ant Acromyrmex echinatior - Li, Qiye (Nature Pub. Group, 2014)
Eusocial insects have evolved the capacity to generate adults with distinct morphological, reproductive and behavioural phenotypes from the same genome. Recent studies suggest that RNA editing might enhance the diversity of gene products at the post-transcriptional level, particularly to induce functional changes in the nervous system. Using head samples from the leaf-cutting ant Acromyrmex echinatior, we compare RNA editomes across eusocial castes, identifying ca. 11,000 RNA editing sites in gynes, large workers and small workers. Those editing sites map to 800 genes functionally enriched for neurotransmission, circadian rhythm, temperature response, RNA splicing and carboxylic acid biosynthesis. Most A. echinatior editing sites are species specific, but 8–23% are conserved across ant subfamilies and likely to have been important for the evolution of eusociality in ants. The level of editing varies for the same site between castes, suggesting that RNA editing might be a general mechanism that shapes caste behaviour in ants.